Z-Theory. The Ultimate Paradigm Shift (Global Journal of Science Frontier Research, 2019)
Application of Z-Theory to the area where Relativity was born leads to another way of comprehension with more in-depth analysis of all relevant physical phenomena. The result appears as a new set of categories in the human mind that establishes a proper relationship with physical entities and their attributes. Some of them like pure Space and Time (attribute-lack categories) become redundant and should not be used in science any longer.